CAMELLIA SPHAMII (THEACEAE, SECT. PIQUETIA), A NEW TAXON OF YELLOW FLOWER FROM LANGBIANG BIOSPHERE RESERVE, VIETNAM - Quang Cuong Truong; Van Huong Le; Van Son Le; Quang Minh Le; Gia Hoang; Hong Truong Luu (Tạp chí Khoa học Đại học Đà Lạt)
Camellia sphamii is described and illustrated as a new species of section Piquetia from Hamasin village, D’ran town, Don Duong district, Lam Dong province, Vietnam. C. sphamii is similar to C. proensis (Quach, Luong et al., 2021) but differs from it in several morphological features: mature leaves cordate at base, young leaves purple; pericarp 7–8 mm thick with dense hair on the outer surface, flower buds ovate, ferruginous; sepals 5, hemisphere, concave, finely hairy on the outer surface, sparsely hairy on the inside, petals 7, finely hairy on the outer surface, with translucent margin, concave; style 5, ½ basally united; capsule 5 locular. Information on its phenology, distribution, ecology, and conservation status is also provided.